Formation of C-C and C-O bonds and oxygen removal in reactions of alkanediols, alkanols, and alkanals on copper catalysts - Sad, Maria Eugenia (2011)
This study reports evidence for catalytic deoxygenation of alkanols, alkanals, and alkanediols on dispersed Cu clusters with minimal use of external H 2 and with the concurrent formation of new C-C and C-O bonds. These catalysts selectively remove O-atoms from these oxygenates as CO or CO 2 through decarbonylation or decarboxylation routes, respectively, that use C-atoms present within reactants or as H 2O using H 2 added or formed in situ from CO/H 2O mixtures via water-gas shift. Cu catalysts fully convert 1,3-propanediol to equilibrated propanol-propanal intermediates that subsequently form larger oxygenates via aldol-type condensation and esterification routes without detectable involvement of the oxide supports. Propanal-propanol-H 2 equilibration is mediated by their chemisorption and interconversion at surfaces via C-H and O-H activation and propoxide intermediates. The kinetic effects of H 2, propanal, and propanol pressures on turnover rates, taken together with measured selectivities and the established chemical events for base-catalyzed condensation and esterification reactions, indicate that both reactions involve kinetically relevant bimolecular steps in which propoxide species, acting as the base, abstract the α-hydrogen in adsorbed propanal (condensation) or attack the electrophilic C-atom at its carbonyl group (esterification). These weakly held basic alkoxides render Cu surfaces able to mediate C-C and C-O formation reactions typically catalyzed by basic sites inherent in the catalyst, instead of provided by coadsorbed organic moieties. Turnover rates for condensation and esterification reactions decrease with increasing Cu dispersion, because low-coordination corner and edge atoms prevalent on small clusters stabilize adsorbed intermediates and increase the activation barriers for the bimolecular kinetically relevant steps required for both reactions.